An Analysis of the Quality of Public Services based on the Application of Local Tax Reporting Information System (Study on Local Tax and Retribution UPTD of Rawalumbu in the Year of 2019) - Renisya Ayu; Krishantoro Krishantoro; Diana Prihadini; Fika Andrianasari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The objectives of this study were to find out the quality of public services based on SIPDAH application on Local Tax and Retribution UPTD of Rawalumbu, obstacles occurred in the   public services based on SIPDAH application on Local Tax and Retribution UPTD of Rawalumbu, and solutions taken in overcoming various obstacles of public services based on SIPDAH application on Local Tax and Retribution UPTD of Rawalumbu in the year of 2019. This research employed a qualitative method. The techniques used for the data collection were literature studies, interviews, and documentation. The data were analyzed by using data reduction, data triangulation, and conclusion withdrawals. The results of the discussion are as follows. First, the quality of public services based on SIPDAH application on UPTD Local Tax and Retribution of Rawalumbu has been good. Second, some obstacles occurred in the quality of public services based on SIPDAH application on UPTD Local Tax and Retribution of Rawalumbu were some local taxpayers did not understand the procedures of SIPDAH online application system, sometimes the connectivity of the SIPDAH application was interrupted (offline), and the SIPDAH application applies lock by the      system or automatically blocked if the local taxpayers were late in the data entry. Finally, the solutions were by updating the features of SIPDAH application to make it easier, the socialization of the local regulation about online local tax reporting, and the cooperative tax authorities should help taxpayers if there were problems.